2020
DOI: 10.1136/bmjpo-2020-000717
|View full text |Cite
|
Sign up to set email alerts
|

Consensus guidelines on managing Rett syndrome across the lifespan

Abstract: BackgroundRett syndrome (RTT) is a severe neurodevelopmental disorder with complex medical comorbidities extending beyond the nervous system requiring the attention of health professionals. There is no peer-reviewed, consensus-based therapeutic guidance to care in RTT. The objective was to provide consensus on guidance of best practice for addressing these concerns.MethodsInformed by the literature and using a modified Delphi approach, a consensus process was used to develop guidance for care in RTT by health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 117 publications
2
36
0
3
Order By: Relevance
“…Despite these efforts, interventions to reduce stereotypic hand movements have not been systematised. In approaches for the management and treatment of Rett syndrome, Fu et al (2020) reported that occupational or physical therapists may prescribe elbow or hand splints to prevent skin breakdown from mouthing. Therefore, the use of a splint is considered to be the closest to a standard intervention for stereotypic hand movements in children with Rett syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these efforts, interventions to reduce stereotypic hand movements have not been systematised. In approaches for the management and treatment of Rett syndrome, Fu et al (2020) reported that occupational or physical therapists may prescribe elbow or hand splints to prevent skin breakdown from mouthing. Therefore, the use of a splint is considered to be the closest to a standard intervention for stereotypic hand movements in children with Rett syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Consensus guidelines for the approach to screening and management of scoliosis and osteopenia are not available for CDD however a consensus of routine management for optimal bone health in Rett syndrome has been developed and is likely relevant to individuals with CDD until higher level evidence becomes available (25,(67)(68)(69).…”
Section: Surveymentioning
confidence: 99%
“…In the assessment of a patient with RTT, sleep must be considered among the areas of evaluation and its characteristics must be investigated. Also laboratory investigations (ferritin, transferrin, serum iron) should be considered in case of disturbed sleep or restless leg syndrome ( 86 ).…”
Section: Sleep Disorders In Rett Syndrome and Rett-related Syndromementioning
confidence: 99%